CHALLENGES IN COCOA CULTIVATION: IN-DEPTH ANALYSIS OF DROUGHT IMPACT IN GHANA'S FOREST-SAVANNAH TRANSITION ZONE - Mensah , Samuel Osei (Ayden Journal of Agriculture and Allied Studies, 2024)
Cocoa production is highly sensitive to climate change, with rainfall patterns playing a crucial role in cocoa yield. Poor rainfall distribution has led to increased droughts and seedling mortality, adversely affecting flower stability, pod development, and ultimately cocoa production. Climate change projections indicate that these conditions will worsen, particularly in West Africa, where drying trends are expected to continue. The anticipated rise in global temperatures and the subsequent increase in potential evapotranspiration (ETp) will exacerbate the hydrological cycle and drought stress on cocoa crops. Water deficits in mature cocoa plants have a detrimental impact on yields and make them susceptible to pests like capsids. Cocoa trees thrive in temperatures ranging from 18-21°C minimum to 30-32°C maximum, with a preference for temperatures between 29-32°C. Higher temperatures, especially during the seedling stage, can be detrimental to cocoa plants. In regions where mean annual rainfall falls below 1250 mm, the loss of moisture due to evapotranspiration can surpass precipitation levels, leading to prolonged droughts during critical growth stages.